BELAS KASIH ALLAH DAN PARTISIPASI ORANG KRISTIANI MENUJU KESELAMATAN : Konsep Keselamatan Dalam Kitab Yunus - Simatupang, Edwind Satri (Aggiornamento, 2024)
This study focuses on the text of Jonah about God's saving work towards Jonah and the Ninevites. The journey of Jonah and the people of Nineveh brought the grace of salvation solely because of God's mercy in withholding His judgement on their disobedience. It also looks at the relevance of salvation for Christians today. The purpose of this article is to make a theological contribution to the vocation of Christians as believers to understand the concept of salvation. The methodology of this article uses a literature study by collecting actual and contextual sources from the Book of Jonah and the lives of Christians today with critical reflection. The research found that achieving salvation requires faith, repentance, humility, obedience and perseverance in prayer. The relevance of this research for Christians today is the guarantee of eternal salvation. The merciful God must be understood as a saving grace. Therefore, the participation and co-operation of humans to receive the grace of salvation is a fundamental task.